2014
DOI: 10.1021/ja411715v
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Direct Arylation of C(sp3)–H Bonds in Aliphatic Amides via Bidentate-Chelation Assistance

Abstract: The Ni-catalyzed, direct arylation of C(sp(3))-H (methyl and methylene) bonds in aliphatic amides containing an 8-aminoquinoline moiety as a bidentate directing group with aryl halides is described. Deuterium-labeling experiments indicate that the C-H bond cleavage step is fast and reversible. Various nickel complexes including both Ni(II) and Ni(0) show a high catalytic activity. The results of a series of mechanistic experiments indicate that the catalytic reaction does not proceed through a Ni(0)/Ni(II) cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
106
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 381 publications
(111 citation statements)
references
References 59 publications
2
106
1
2
Order By: Relevance
“…[14] Va rious functionalities can be incorporated into the molecule at these unactivated CÀHb onds.T his is exemplified by initial reports from the groups of Chatani and Ge.B yu sing Ni II as ap recatalyst in conjunction with [91] or alkylation with alkyl iodides. [92] Shi and co-workers showed the Ni II -catalyzed alkenylation of amide 191 with vinyl iodides [93] to afford alkenylated products.Asreported by Zhang and co-workers, alkenylation can also be accomplished with phenylacetylenes.…”
Section: Nickel(ii)mentioning
confidence: 99%
“…[14] Va rious functionalities can be incorporated into the molecule at these unactivated CÀHb onds.T his is exemplified by initial reports from the groups of Chatani and Ge.B yu sing Ni II as ap recatalyst in conjunction with [91] or alkylation with alkyl iodides. [92] Shi and co-workers showed the Ni II -catalyzed alkenylation of amide 191 with vinyl iodides [93] to afford alkenylated products.Asreported by Zhang and co-workers, alkenylation can also be accomplished with phenylacetylenes.…”
Section: Nickel(ii)mentioning
confidence: 99%
“…In the field of chelation-assisted CH functionalization, our group recently reported on the first nickel(II)-catalyzed β-arylation of unactivated CH bonds of aliphatic amides, using an 8-aminoquinoline moiety as the bidentate directing group and iodoarenes as coupling partners. 27 Prior to our discovery, to the best of our knowledge, nickel-catalyzed C(sp 3 )H bond functionalization had been limited to only one example, namely, the Ni(0)-catalyzed cycloaddition of formamides with alkynes. 28 After the determining the optimized reaction conditions, it was found that 157 afforded the desired product 162 in 83% yield with Ni(OTf) 2 as the precatalyst with the aid of a sterically bulky carboxylic acid (MesCO 2 H) and a base (Na 2 CO 3 ) in DMF at 140°C for 24 h (Scheme 9).…”
Section: C(spmentioning
confidence: 99%
“…Significant deuterium incorporation was also found at C2',t hus indicating that the nickel(0) system can also activate the N-benzylic position. [15] For 1a to 3a (84 %Y ield), GCMS analysis of the crude reaction mixture revealed the concomitant formation of benzaldehyde in 78 %yield. These observations show that the benzyloxy unit of the acrylate partner (2b)a cts as the reductant for C À Cbond formation.…”
Section: Angewandte Chemiementioning
confidence: 99%